2021
DOI: 10.1021/acs.est.0c08093
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants (POPs) and Related Chemicals in the Global Environment: Some Personal Reflections

Abstract: What are POPs and why are they interesting and important?In this article, I have been given the chance to 'tell the story' of POPs, through personal reflections on how the field has developed. I hope I can do that by conveying some of the sense of excitement, interest and importance for the environment and society that motivated me as a young research scientist and reflect on some of the ongoing needs and priorities for the environmental chemistry and chemicals management fields.Persistent organic pollutants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(53 citation statements)
references
References 147 publications
0
53
0
Order By: Relevance
“…Dien et al [20] performed a large scale of panel data analysis of POPs in the air in Japan and found numerous external factors affecting POPs distribution. In addition, some scholars have done lots of analysis and researches on other characteristics of POPs [29,30].…”
Section: Related Workmentioning
confidence: 99%
“…Dien et al [20] performed a large scale of panel data analysis of POPs in the air in Japan and found numerous external factors affecting POPs distribution. In addition, some scholars have done lots of analysis and researches on other characteristics of POPs [29,30].…”
Section: Related Workmentioning
confidence: 99%
“…Legacy persistent organic pollutants (POPs) such as organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) are of major concern for public health owing to their persistence, carcinogenicity, bioaccumulation, and the ability for long-range atmospheric transport ( Jones, 2021 , Lohmann et al, 2007 ). As a consequence of the ubiquitous presence and harmful ecological impacts, several pesticidal POPs such as α , β - and γ -hexacholorocyclohexane isomers (HCH), Lindane (>99% γ -HCH) and endosulfan in the pre-existing list of the “dirty dozen” are included under the category of new POPs by the Stockholm Convention ( UNEP, 2001 , UNEP, 2008 , UNEP, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides (OCPs) are persistent organic environmental pollutants that bioaccumulate in food chains. Although some OCPs have been banned or restricted for decades, their extensive usage, long half-lives, and bioaccumulation still affect human health 3 . Previous studies have shown that OCPs may cause immune dysfunction, endocrine disruption, neurobehavioral and cognitive impairment, and may have chronic effects on reproductive potential, as carcinogens 4 8 .…”
Section: Introductionmentioning
confidence: 99%